Activity and substrate specificity of Candida, Aspergillus, and Coccidioides Tpt1: essential tRNA splicing enzymes and potential antifungal targets - Dantuluri, Swathi (RNA, 2021)
The enzyme Tpt1 is an essential agent of fungal tRNA splicing that removes an internal RNA 2′-PO(4) generated by fungal tRNA ligase. Tpt1 performs a two-step reaction in which: (i) the 2′-PO(4) attacks NAD(+) to form an RNA-2′-phospho-(ADP-ribose) intermediate; and (ii) transesterification of the ADP-ribose O2″ to the RNA 2′-phosphodiester yields 2′-OH RNA and ADP-ribose-1″,2″-cyclic phosphate. Because Tpt1 does not participate in metazoan tRNA splicing, and Tpt1 knockout has no apparent impact on mammalian physiology, Tpt1 is considered a potential antifungal drug target. Here we characterize Tpt1 enzymes from four human fungal pathogens: Coccidioides immitis, the agent of Valley Fever; Aspergillus fumigatus and Candida albicans, which cause invasive, often fatal, infections in immunocompromised hosts; and Candida auris, an emerging pathogen that is resistant to current therapies. All four pathogen Tpt1s were active in vivo in complementing a lethal Saccharomyces cerevisiae tpt1Δ mutation and in vitro in NAD(+)-dependent conversion of a 2′-PO(4) to a 2′-OH. The fungal Tpt1s utilized nicotinamide hypoxanthine dinucleotide as a substrate in lieu of NAD(+), albeit with much lower affinity, whereas nicotinic acid adenine dinucleotide was ineffective. Fungal Tpt1s efficiently removed an internal ribonucleotide 2′-phosphate from an otherwise all-DNA substrate. Replacement of an RNA ribose-2′-PO(4) nucleotide with arabinose-2′-PO(4) diminished enzyme specific activity by ≥2000-fold and selectively slowed step 2 of the reaction pathway, resulting in transient accumulation of an ara-2′-phospho-ADP-ribosylated intermediate. Our results implicate the 2′-PO(4) ribonucleotide as the principal determinant of fungal Tpt1 nucleic acid substrate specificity.